Going to the market chance, strategy and success in the lives of Dutch artists (1600-1920) - Kolfin, Elmer 1969- (2022)
The articles in this Oud Holland theme issue ‘Chance, strategy and success in the lives of Dutch artists (1600-1920)’ explore the relationships between chance, success and strategic choices in the careers of artists from the Netherlands. Chance is a relatively little researched phenomenon in socioeconomic art history, but proves to have been a major theme for artists. In seeking to shape their careers, they deliberately sought out circumstances in which they could engineer as many opportunities for success as possible. Their awareness of what it would take to achieve this is found to be both remarkably consistent and in keeping with modern theories that describe success as a social phenomenon, namely that of active networking. Their strategies are associated with various forms of mobility. The essays in this issue draw on seventeenth and eighteenth-century art literature and on notable artists such as Herman Saftleven (1609-1685), Cornelis van Spaendonck (1756-1839), Hendrik Willem Mesdag (1831-1915) and Piet Mondrian (1872-1944). The authors investigate how network strategies are deployed to avoid leaving success to chance and to orchestrate it – or at least render it possible – through one’s own actions. In pursuit of connections, artists have systematically travelled to locales where they expect to find ample opportunities: to meet fellow artists and see other works of art so as to further develop their own; to display their own work; and to find private and institutional buyers, ideally in a consistent flow. Success can then appear natural at times, but this is far from accurate. Art historians that report in texts on processes of this kind tend to emphasise the element of necessity. However, the sources they work with, the literary genres they draw on and the field to which they belong generate narratives that are inherently bound by causal relationships, obscuring the underlying contingency.
Keywords: Geschichte 1600-1920; Zufall; Netzwerk; Künstler; Erfolg; Mobilität; Niederlande